Professional narratives in mathematics teacher education - Ponte, João Pedro da (2011)
In recent years, narratives gained prominence in many educational fields, especially in teacher education and in research on teaching. In this paper I discuss why narratives may be of interest both for mathematics teachers’ professional development and for researchers that investigate teachers’ professional knowledge.